Synthesis of Aryl(TMP)iodonium Salts and Their Arylation Reactions - Stuart, David R. (Synlett, 2025)
Diaryliodonium salts continue to emerge as versatile arylation reagents. This is especially true for unsymmetrical aryl(TMP)iodonium salts (TMP = 2,4,6-trimethoxyphenyl) because they undergo highly selective aryl transfer across diverse mechanistic settings. This account outlines our motivation for exploring the chemistry of aryl(TMP)iodonium salts and our efforts to develop streamlined synthetic methods to access them and the novel arylation reactions that use them.
Keywords: diaryliodonium; arylation; ligand coupling; aryne; metal-free